2015
DOI: 10.1016/j.pec.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Provider communication quality: Influence of patients’ weight and race

Abstract: Objective To examine the relationship between patient weight and provider communication quality and determine whether patient race/ethnicity modifies this association. Methods We conducted a cross-sectional analysis with 2009-2010 Medical Expenditures Panel Survey – Household Component (N = 25,971). Our dependent variables were patient report of providers explaining well, listening, showing respect, and spending time. Our independent variables were patient weight status and patient weight-race/ethnicity grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 46 publications
2
31
1
Order By: Relevance
“…Our finding that parents of obese NH Black children were more likely to report that healthcare providers always listened carefully compared to parents of non-obese NH White differs from a previous study among adults, which found that obese NH Black patients experience worse communication quality than non-obese NH Whites [30]. Taken together, these findings suggest that relationships among race, weight, and healthcare provider communication quality differ in pediatric and adult patient populations.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Our finding that parents of obese NH Black children were more likely to report that healthcare providers always listened carefully compared to parents of non-obese NH White differs from a previous study among adults, which found that obese NH Black patients experience worse communication quality than non-obese NH Whites [30]. Taken together, these findings suggest that relationships among race, weight, and healthcare provider communication quality differ in pediatric and adult patient populations.…”
Section: Discussioncontrasting
confidence: 66%
“…Our results suggest that the relationship between obesity status and healthcare provider communication quality may differ for pediatric and adults patients. Research among adults has reported that the communication and relationships of obese patients with their healthcare providers are either similar [30, 36], or worse when compared to their healthy weight counterparts [14, 15, 18, 37]. One possible explanation for this difference is that healthcare providers may be more sympathetic towards parents of obese children because they perceive a higher likelihood of successfully addressing weight issues compared to obese adult patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of provider attitudes [5, 79], patient experiences [10, 11, 54], and access to women’s health services [12, 13, 55], suggest that body weight affects the quality of care women receive. This study provides new evidence to support those conclusions and further suggests that increased use of patient-centered communication can strengthen therapeutic relationships and enhance the quality of prenatal care for women with overweight and obesity.…”
Section: 0 Discussion and Conclusionmentioning
confidence: 99%
“…Moreover, minority physicians were more likely to prescribe preventive screening tests and counseling than white physicians [27]. Obese or overweight blacks were found to be less likely to report that their providers explained things well or spent enough time with them [28]. It is not clear why patients would have higher odds of recalling being given weight-related advice from minority HCPs than from white HCPs.…”
Section: Discussionmentioning
confidence: 99%